Electromagnetic shielding effectiveness of gypsum-magnetite composite at x-band frequency - Mohamad Ashry, Jusoh; Yeow, Y. K.; Rodziah, Nazlan; Fahmiruddin, Esa (Electromagnetics Academy, 2019)
Rapid development of the electronic industry has increased the frequency of communication devices which lead to higher intensity of electromagnetic (EM) wave production. Too much exposure of EM wave can cause harm to health besides imposing disturbances in performances of other electronic devices. Hence, this research studies the structural and electromagnetic properties of materials that can act as electromagnetic shielding material at x-band frequency. Different compositions of magnetite powder/Fe3O4 (0, 10, 20 and 100 wt.%) were prepared to be dispersed in gypsum powders to form gypsum-magnetite composites. The structural properties of composites were characterized using Scanning Electron Microscopy (SEM) to observe homogeneity of the composites. The X-Ray Diffraction (XRD) was used to determine phase composition of the gypsum-magnetite composites. Scattering parameters of reflection coefficient, S11, and transmission coefficient, S21, were measured using Vector Network Analyzer (VNA). These parameters will be used to calculate the shielding effectiveness (SE) of gypsum-magnetite composite at x-band frequency. The results show that the total SE of the gypsum-magnetite composites were increased by adding magnetite powders.